Pengembangan Produk Olahan Ikan dalam Upaya Pemanfaatan Hasil Tangkapan Ikan Tuna di Desa Sumberjaya, Sumur, Pandeglang - Pipin Supinah; Bustami; Muhammad Dwiki Amara Ermaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Sumberjaya Village is one of the villages that have potential for capture fisheries in Pandeglang Regency, Banten Province. Sumberjaya village catches are small pelagic fish and large pelagic fish. The processing of fishery products in this village is only salting anchovy, therefore it is necessary to diversify fish preparations to increase the sale value of the product. This program aims to empower the community by providing assistance in fishery product development activities in Sumberjaya Village, Sumur District, Pandeglang Regency, Banten. The method used is a participatory method, where the community was placed as a subject in every activity, ranging from planning, implementation, and evaluation. Sumberjaya Village is one of the villages that have potential for capture fisheries in Pandeglang Regency, Banten Province. Sumberjaya village catches are small pelagic fish and large pelagic fish. The processing of fishery products in this village is only salting anchovy, therefore it is necessary to diversify fish preparations to increase the sale value of the product. This program aims to empower the community by providing assistance in fishery product development activities in Sumberjaya Village, Sumur District, Pandeglang Regency, Banten. The method used is a participatory method, where the community was placed as a subject in every activity, ranging from planning, implementation, and evaluation. Key word: Sumberjaya village, fish nugget, processing raw materials, Fishery Product, Community assistance